Sistema de control interno en la cuenta de inventario de la Empresa ABC - Burgos Saquicela, Ana Mercedes (2025)
This work entitled: Internal Control System in the Inventory Account of the ABC Company, deals with how the absence of internal control in inventories negatively affects the financial and economic results of the company. This research is carried out in a commercial company, where a considerable amount of products are handled that are bought and sold, and that has problems in the internal control of inventories. A mixed approach was used: qualitative and quantitative and the methodology was inductive, three interviews were conducted with experts in accounting, finance and taxation, an observation of the inventory processes and documentary analysis to learn about the internal control of inventories and their impact on the financial statements of the ABC company. To support this research, topics such as: inventory control system, inventory valuation methods, order policies, distribution procedures, physical inventory controls, among others related to stocks, supporting the importance of control and its application. A proposal was designed detailing an internal control system in stages one: diagnose, stage two, establish guidelines for the inventory system and stage three, validate where control policies are applied, product distribution, procedures and flowcharts in order to improve the company's operational resources and maintain the necessary inventories in stock for its production or sale, conclusions and recommendations are made to improve inventory control and its related areas.